2022
DOI: 10.1039/d2ta02930h
|View full text |Cite
|
Sign up to set email alerts
|

Defect engineering of electrode materials towards superior reaction kinetics for high-performance supercapacitors

Abstract: In this review, a comprehensive overview of recent progress and achievements in defect engineering of electrode materials towards superior reaction kinetics for supercapacitors are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 199 publications
0
30
0
Order By: Relevance
“…Various energy conversion/storage techniques, ranging from fuel cells to metal-air batteries, have been developed in response to energy demands and environmental concerns. [1][2][3][4] Rechargeable Zn-air batteries (RZABs) have been hailed as one transition metal/carbon arrays, [18,19] some of which even surpass the performance of commercial noble-metal-based materials (RuO 2 , Pt/C). [15,20] However, the electrochemical activity development of RZABs is still confined, since the actual working environment of cathode catalysts in assembled battery differs from the test environment in half-cell tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various energy conversion/storage techniques, ranging from fuel cells to metal-air batteries, have been developed in response to energy demands and environmental concerns. [1][2][3][4] Rechargeable Zn-air batteries (RZABs) have been hailed as one transition metal/carbon arrays, [18,19] some of which even surpass the performance of commercial noble-metal-based materials (RuO 2 , Pt/C). [15,20] However, the electrochemical activity development of RZABs is still confined, since the actual working environment of cathode catalysts in assembled battery differs from the test environment in half-cell tests.…”
Section: Introductionmentioning
confidence: 99%
“…Various energy conversion/storage techniques, ranging from fuel cells to metal–air batteries, have been developed in response to energy demands and environmental concerns. [ 1–4 ] Rechargeable Zn–air batteries (RZABs) have been hailed as one of the promising advanced energy devices due to their large theoretical energy density, low price, eco‐friendliness, and high safety. [ 5,6 ] Generally, RZABs are made of an air cathode and a Zn anode packaged with an alkaline electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…22 On the other hand, theoretical studies have also confirmed that vacancy modification can increase the active sites and reduce the catalytic energy barrier, thus reducing the Gibbs free energies of the elementary reaction stage and ultimately improving its electrocatalytic performance. 23,24 Currently, an oxygen vacancy is considered as an effective anion vacancy to promote OER activity [25][26][27] because oxygen vacancy can not only change the electron distribution on the surface of spinel but also decrease the adsorption energy of the OH* free radical, thereby improving the activity of catalytic reaction sites. 28,29 Xie et al reported NiCo 2 O 4 ultrathin nanosheets with oxygen-rich vacancies by calcination in air, and the introduction of oxygen vacancies increases the number of active sites and reduces the reaction energy barrier, which effectively improves the OER activity of NiCo 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…22 On the other hand, theoretical studies have also confirmed that vacancy modification can increase the active sites and reduce the catalytic energy barrier, thus reducing the Gibbs free energies of the elementary reaction stage and ultimately improving its electrocatalytic performance. 23,24…”
Section: Introductionmentioning
confidence: 99%
“…Supercapacitors, which hold the advantages of high power density, rapid charging, and long service life, stand out from many novel energy storage devices. [5][6][7] Nevertheless, low energy density is regarded as a severe deficiency of supercapacitors, which dramatically limits their practical application. 8 Hybrid supercapacitors, composed of capacitive anodes and battery-type cathodes, are identified as promising energy storage devices of the future.…”
Section: Introductionmentioning
confidence: 99%